Implementation Of The Independent Curriculum On Physical Education Learning At Junior High School - Hesti Nur Utami; Novial Azhar; Tata Abdul Fatah; Ega Trisna Rahayu (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Learning is an activity carried out in two directions to achieve learning goals efficiently and effectively. Implementation of the Independent Learning Curriculum in PJOK subjects at SMPIT Abdan Syakuro Lampu Iman has implemented the Independent Learning Curriculum in stages and has implemented Project Based Learning which is one of the learning activities in the Independent Learning Curriculum. The obstacle in implementing the Independent Learning Curriculum in PJOK subjects at SMPIT Abdan Syakuro Lampu Iman is that teachers still find it difficult to instil the 6 Pancasila Student Profile characters in students with the various characteristics that each student has. Apart from that, from the observations made by researchers, it is also clear that teachers have not been able to get out of their comfort zone in teaching as it can be seen that in teaching they are still comfortable with using the same methods and there is still a lack of teacher ability in using learning media, this can be seen when teachers teach Most just explain the material and then give assignments to students. The solution used in implementing the Merdeka Belajar Curriculum in PJOK subjects at SMPIT Abdan Syakuro Lampu Iman is that teachers look for information or references about learning assessments and regularly participate in training on the implementation of the Merdeka Belajar Curriculum which is held.